Practical english grammar part 1 [ - Lesson For Life International (Melburne : Lesson For Life International, 2000)
System requirements: Intel Pentium/Celeron/AMD 233Hz or faster; Windows XP, ME, 2000, 98 NT4; 16 MB RAM; 1024x768 resolution; 2xCD-ROM/DVD-ROM drive; 16 bit Windows compatible sound card; 100MB disk space
Fast and fun way to learn English - Perfect for personal, educational or business use
Keywords: English language -- Grammar -- Software; English language -- Remedial teaching -- Software; English language -- Study and teaching -- Foreign speakers -- Software